Translating and Interpreting George Orwell in Ukraine: A Study of Literary and Critical Engagement - Malyshivska, Iryna; Livingstone, David (American & British Studies Annual, 2025)
This article explores the different ways George Orwell’s works have entered Ukrainian culture, with a particular focus on the translations that have introduced his sharp political commentary to Ukrainian readers. Apart from translations, we will examine other channels of interpretation, such as various adaptations and critical analyses, which have further expanded Orwell’s reach and influence in Ukraine. By analyzing these various forms of transmission, we would like to shed light on how Orwell’s themes have resonated in a Ukrainian context, and how his works continue to inspire reflection and discourse in a nation with its own complex history of sociopolitical struggle. This study represents the first attempt to gather and analyze the various interpretations of Orwell’s legacy within Ukraine.